Seychelles : Fourth and Fifth Reviews Under the Extended Arrangement and Request for Modification and Waiver of Applicability of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Seychelles. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper discusses Seychelles' Fourth and Fifth Reviews under the Extended Arrangement and Request for Modification and Waiver of Applicability of Performance Criteria. All performance criteria as of December 31, 2015, and June 30, 2016, were met, and the macroeconomic program remains broadly on track for the second half of the year. The structural agenda is proceeding, albeit with some technical delays. The IMF staff welcomes the authorities' commitment to the goal of a steady reduction in public debt over the medium term reflected in the draft 2017 budget.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet